Ghrelin and NUCB2/Nesfatin-1 Co-Localization With Digestive Enzymes in the Intestine of Pejerrey (Odontesthes bonariensis) - Bertucci, Juan Ignacio (2019)
Ghrelin (orexigenic) and nesfatin-1 (anorexigenic) are two peptides with opposing actions on food intake regulation and are mainly expressed in the hypothalamus and gut of mammals and fish. Both are involved in the regulation of a wide range of physiological processes in vertebrates, including metabolism, growth, and reproduction. However, the anatomical relationship between these peptides and the nutrient assimilation processes are not well understood. Thus, the aim of this work was to determine the localization of ghrelin, nesfatin-1, and several enzymes involved in the digestive process (lipoprotein lipase, aminopeptidase A, trypsin, and sucrase-isomaltase) in the intestine of pejerrey (Odontesthes bonariensis), a species with commercial importance in South America. We observed co-localization of ghrelin and nesfatin-1 in enteroendocrine cells, absorptive cells, and in cells of the lamina propia. Approximately half of the cells displaying ghrelin-like immunoreactivity co-localized the NUCB2/nesfatin-1-like signal. In addition, both peptides showed co-localization with lipoprotein lipase, aminopeptidase A, trypsin, or sucrase-isomaltase. All digestive enzymes except for aminopeptidase A and trypsin, showed high co-localization (68–88%) with both ghrelin-like and NUCB2/nesfatin-1-like signals in absorptive, enteroendocrine, and lamina propria cells. Together, our results provide immunohistochemical evidence supporting a role for both ghrelin and NUCB2/nesfatin-1 in the regulation of nutrient assimilation in fish.